Factors influencing the adoption and effectiveness of online training program on female faculty members competencies in Saudi Arabian public universities - Alhaidan, Homoud Freh (2020)
A good number of researchers have demonstrated the need for online training for the faculty members in various countries around the world in recent years. However, most of these academic researchers have discussed the different effects of the online training system. Conversely, the need for online training for female faculty members in Saudi Arabia has not been adequately measured, which is culturally very diverse and unique. Thus, empirical evidence is clearly lacking and needs to be studied. There is also no conclusive model for Saudi Arabian educational industry yet exists. As gender inequity remains an unsolved issue in Saudi Arabia, thus, this research is undertaken to realise the need to examine the need for the online training program (OTP) for Saudi women faculty members closely. Therefore, this research aims to determine the factors influencing the adoption of the online training program and its effectiveness for the female faculty members in Saudi Arabian public universities. At the beginning of the study, issues were identified, goals and objectives were set, and a detailed review of the literature was conducted to identify the variables for this study. The theoretical foundation of this research is based on Ajzen’s Theory of Planned Behavior (TPB) and Venkatesh and Davis’s Technology Acceptance Model (TAM). Besides, in this study, “social influence” has been added as a dependent variable as well as “competitive pressure” and “government regulations” were added as moderator that signifies the theoretical extansion of this study. For this research, primary data has been collected from female faculty members working in different Saudi Arabian public universities using simple random sampling method. A self-administered closed-ended questionnaire was utilised to collect data from 228 randomly selected respondents. Before actual data collection, a pilot study was conducted on a small sample group of female faculty members to clarify the statement of the survey questionnaire. Finally, PLS-SEM was used to run the analysis. The findings show that perceived ease of use, perceived usefulness, perceived relative advantage, and social influence has a significant positive relationship with adoption of OTP and effectiveness of OTP. However, the variable “perceived trust” was not statistically significant. Besides, the testing of two new moderating variables (competitive pressure and government regulations) has also confirmed that these two variables significantly influence the relationship between adoption of OTP and effectiveness of OTP for the female faculty members working in different Saudi Arabian public universities. This statistical significance has provided new light for future consideration. This study has significantly contributed to the theoretical enhancement of the online training program (OTP) theory by adding “social influence” factor in the context of the adoption of the online training program. Hence, this eventually extends the understanding of the current model and opens a new direction for further investigation. This finding will further facilitate future policy development for Saudi Arabia’s education industry by offering better employment opportunities for the female workforce. It can also function as an essential guideline for universities to enhance employee motivation and conjointly to retain staff with high potential and talent within the setting of the Kingdom of Saudi Arabia. Finally, study limitations are discussed, and future study directions are proposed.